Current status and future prospects of renewable and sustainable energy in North America: Progress and challenges. (1st October 2022) - Azarpour, Abbas; Mohammadzadeh, Omid; Rezaei, Nima; Zendehboudi, Sohrab
Graphical abstract: Highlights: A comprehensive study on renewable energy resources in North America is conducted. A detailed evaluation of renewable energy potentials is provided. Important steps for better use of renewable energy resources are summarized. Emerging technologies for development and management of renewable energy are addressed. Theoretical and practical challenges in development of renewable energies are highlighted. Abstract: Energy is an important drive for the economic development and social growth. The energy demand has remarkably escalated due to the technological developments in various governmental, industrial, and municipal activities. The fast growing rate of the energy demand as well as the fuel prices, along with the necessity to control the greenhouse gas emissions are the leading driving forces for effective exploitation of the renewable energy resources. In fact, satisfying the growing global energy demands and mitigating the climate change are of the utmost importance in the modern days. In this review paper, a detailed overview of the development and evolution of the renewable and sustainable energy sources is provided in terms of their types, characteristics, applications, production processes, advantages and disadvantages. Moreover, we discuss the impacts of the renewable energies on health and environment, along with the relevant policies and regulations. Further, the emerging technologies and theoretical and practical challenges in the development of the renewable energies are analyzed. Particularly, this review provides information on renewable and sustainable energies' status and prospects in North America. Central large-scale technology and distributed configurations of the renewable energies might be improved in the North American countries to effectively utilize the renewable energies for producing electricity, biomass-based fuels, and heating in both local/rural and industrial divisions. In addition to employment opportunities stemmed from manufacturing of the renewable energies, its significant impact on the economic development can be enhanced in the US, Canada, and Mexico through development of the renewable energy sources.